Do 'we' 'do' God? LindaWoodhead & RebeccaCatto (eds), Religion and change in modern Britain. London: Routledge. (7th August 2013) - Coleman, Simon
Abstract : What does it mean to talk of the religion 'of' a given country? I reflect on an edited volume dealing with religion in Britain and consider two related themes: the secular considered as 'absence' or 'presence', and the siting of religion not in conventional denominations or ritual practices but in spaces of encounter between religions, and between the so‐called 'religious' and 'secular'.